Carbon Dots: Synthesis, Properties and Applications - Cui, Lin; Ren, Xin; Sun, Mengtao; Liu, Haiyan; Xia, Lixin (Nanomaterials (Basel, Switzerland), 2021)
Carbon dots (CDs) are known as the rising star of carbon-based nanomaterials and, by virtue of their unique structure and fascinating properties, they have attracted considerable interest in different fields such as biological sensing, drug delivery, photodynamic therapy, photocatalysis, and solar cells in recent years. Particularly, the outstanding electronic and optical properties of the CDs have attracted increasing attention in biomedical and photocatalytic applications owing to their low toxicity, biocompatibility, excellent photostability, tunable fluorescence, outstanding efficient up-converted photoluminescence behavior, and photo-induced electron transfer ability. This article reviews recent progress on the synthesis routes and optical properties of CDs as well as biomedical and photocatalytic applications. Furthermore, we discuss an outlook on future and potential development of the CDs based biosensor, biological dye, biological vehicle, and photocatalysts in this booming research field.